Microbiological Indication Of Differently Salinated Soils In Termiz District (Texas Journal of Agriculture and Biological Sciences, 2025)
Microbiology studies microorganisms that are very small, invisible to the naked eye, and visible only with the help of optical instruments - light or electron microscopes. Microbiology is a science that studies the morphology, physiology, biochemistry, genetics, ecology and systematics of microscopic fungi, bacteria, mycoplasmas, viruses, actinomycetes and microscopic algae. Microbiology is a relatively young branch of biology, which is growing and developing every day. The modern science of soil diagnostics uses the achievements of such sections of soil science as soil morphology, soil chemistry, soil physics and mineralogy. To characterize the soil and its condition, it is closely related to biochemistry, molecular biology, biotechnology, agrochemistry, phytopathology, agriculture, industry, geology, genetics and other sciences. The world of microorganisms is incredibly rich and diverse.